Providing Spiritual Dhikr Therapy to Patients with Sensory Perception Disorders and Auditory Hallucinations - Adista Nur Alifa; Enggal Hadi Kurniyawan; Erti Ikhtiarini Dewi; Amalia Kusumaningsih (KHD Production, 2025)
Hallucinations could cause someone to be unable to distinguish between what was real and what was merely an illusion. During hallucinations, the client could react with suspicion, fear, curiosity, insecurity, anxiety, and confusion. In this case, Mr. H experienced auditory hallucinations in the form of male whispers. Spiritual dhikr therapy could be used as an approach to healing mental illness, emphasizing inner strength. This study aimed to apply spiritual dhikr therapy to patients with sensory perception disorders: auditory hallucinations. The method used was a case study on a patient with hallucinations, with spiritual dhikr therapy intervention provided for 7 days to the patient. The therapy included reciting the phrase